1999
DOI: 10.1111/j.1572-0241.1999.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cancer in The Course of Chronic Pancreatitis

Abstract: The risks of pancreatic and nonpancreatic cancers are increased in the course of chronic pancreatitis, the former being significantly higher than the latter. The very high incidence of pancreatic cancer in smokers probably suggests that, in addition to cigarette smoking, some other factor linked to chronic inflammation of the pancreas may be responsible for the increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 27 publications
3
81
2
7
Order By: Relevance
“…In fact, the standardized incidence ratio was 26.3 (95% CI 19.9-34.2) for all patients, 16.5 (95% CI 11.1-23.7) for patients with two or more years of follow-up, and 14.4 (95% CI 8.5-22.8) for patients with five or more years of follow-up. These data have been confirmed in other reports [51,53,55,60]. We need further studies to reevaluate the real risk rate of pancreatic adenocarcinoma in patients with chronic pancreatitis.…”
Section: C4supporting
confidence: 75%
See 2 more Smart Citations
“…In fact, the standardized incidence ratio was 26.3 (95% CI 19.9-34.2) for all patients, 16.5 (95% CI 11.1-23.7) for patients with two or more years of follow-up, and 14.4 (95% CI 8.5-22.8) for patients with five or more years of follow-up. These data have been confirmed in other reports [51,53,55,60]. We need further studies to reevaluate the real risk rate of pancreatic adenocarcinoma in patients with chronic pancreatitis.…”
Section: C4supporting
confidence: 75%
“…Cohort studies [52][53][54][55][56][57][58][59][60] confirmed the relationship between chronic pancreatitis and pancreatic cancer. It should be underlined that the findings of the cohort studies must be viewed in the light of potential methodological problems: first, the recruitment of patients began from 1946 to 1973 in most studies [53][54][55][56]59,60], when it was difficult to distinguish chronic pancreatitis from pancreatic cancer; second, cancer was not confirmed histologically in all patients evaluated; third, a number of patients may have had a slower-growing cancer, such as a cystadenocarcinoma or intraductal papillary neoplasia. Finally, the possible presence of a misclassification bias is well reported in the study of Lowenfels [56].…”
Section: C4mentioning
confidence: 87%
See 1 more Smart Citation
“…Chronic pancreatitis is also a major risk factor for pancreatic cancer, one of the most intractable conditions (48,49). Our findings revealing a molecular and cellular mechanism behind the reduction in CVB5 load and attenuation of pancreatitis upon IL-33 treatment represent a significant advance in our knowledge in this important medical condition.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, studies of recent years have confirmed chronic pancreatitis to be a premalignant condition leading to pancreatic carcinoma [24,25] .…”
mentioning
confidence: 99%